KEPUTUSAN BERKUNJUNG WISATAWAN DITINJAU DARI PERSPEKTIF HARGA TIKET, CITRA DESTINASI DAN FASILITAS WISATA DI HERITAGE PALACE KARTASURA - Muh. Sugeng Riyadi S; Heni Susilowati (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
The purpose of this study was to determine the effect of ticket prices, destination image, tourist facilities on the decision to visit The Heritage Palace Kartasura. The research sampling technique was purposive sampling of 100 respondents. The data instrument was assessed using a Likert scale that met the validity and reliability requirements. The analysis uses multiple linear regression to test the hypothesis with the t test and F test. The results showed that partially and simultaneously the entrance ticket price, destination image and tourist facilities had a positive and significant effect on the decision to visit The Heritage Palacae Kartasura with a significant value <0.05. The ticket price variable has a dominant influence over the destination image variable and tourist facilities.